New leaders, new dawns? : South Africa and Zimbabwe under Cyril Ramaphosa and Emmerson Mnangagwa - Brown, Chris (Christopher); Moore, David (Lecturer in development studies); Rutherford, Blair A. (Blair Allan), 1965- (McGill-Queen's University Press, 2022)
"In late 2017 and early 2018, South Africa and Zimbabwe both experienced rapid, and unexpected, political transitions. In Zimbabwe, Robert Mugabe, the only leader the country had ever known, was replaced in a "soft coup" by his erstwhile vice-president, Emmerson Mnangagwa. Subsequently, over a twelve-day period in February 2018, South African president Jacob Zuma was prematurely forced from office by his former deputy president, Cyril Ramaphosa. The widespread popular rejoicing that accompanied their arrival compounded the shock of these sudden transitions. New Leaders, New Dawns? explores these political transitions and the way they were received. Contributors consider how former liberation heroes like Mugabe and Zuma could have fallen so low; the underlying reasons for their ouster; what happened to their liberation movements turned ruling parties; and, perhaps most importantly, what the rise to power of Ramaphosa and Mnangagwa foreshadowed. Bringing together fourteen leading international scholars of southern Africa, and adopting a political economy framework, this volume argues that the changes in leadership are welcome, but insufficient. While the time had come for Zuma and Mugabe to go, there is little in the personal histories or early policy actions of Ramaphosa and Mnangagwa that suggests they will be capable of addressing the profound social, economic, and political problems both countries face. New Leaders, New Dawns? reveals that despite what these new leaders may have promised, a "new dawn" has not yet arrived in southern Africa."--